Prognostic Impact of Serum CRP Level in Head and Neck Squamous Cell Carcinoma - Zhang, Yaoting; Gu, Dongsheng (Frontiers in Oncology, 2022)
Objective: This study evaluated the association of pretreatment serum C-reactive protein (CRP) level with prognosis in patients with head and neck squamous cell carcinoma (HNSCC). Methods: Within a single-center retrospective study, HNSCC patients receiving treatment between 2014 and 2016 were analyzed regarding the prognostic value of CRP serum levels. X-Tile software was used to determine the optimal cut-off value of serum CRP level. The log-rank test and Kaplan-Meier method were used to assess the effects of CRP level on prognosis in patients with HNSCC. Univariate and multivariate analyses (enter method) using a Cox proportional hazards model were utilized to identify prognostic indicators of progression-free survival (PFS) as the primary outcome and overall survival (OS) as the secondary outcome. Results: A total of 221 patients with HNSCC were assessed for eligibility; and 208 cases were included in the analysis. HNSCC patients in the low-group (CRP ≤11.3 mg/L) showed better survival than those in the high-group (CRP > 11.3 mg/L). Univariate and multivariate analyses showed that N1-3 stage and a high serum CRP level (> 11.3 mg/L) were unfavorable prognostic factors for PFS and OS in patients with HNSCC. Conclusion: Serum CRP level is an independent prognostic marker for patients with HNSCC. CRP level could be regarded as a novel prognostic factor for HNSCC patients.